The Dynamics of Population Aging and Public Health Expenditure on Economic Growth: An Empirical Study in the Asia-Pacific Region - Puspita Rahayu, Rahma; Nurfitriana Nihayah, Annis (Universitas Negeri Semarang, 2026)
In recent years, empirical studies on population aging have gained significant attention as it has become a major global issue facing both developed and developing countries. Population aging has the potential to exert adverse effects by decreasing labor force participation and productivity among the elderly, as well as causing imbalances between savings and investment that may lead to economic stagnation. Meanwhile, good health plays a crucial role in enhancing human resource quality and economic productivity. The objective of this empirical study is to explore the relationship between population aging, public health expenditure, and economic growth. Utilizing a panel data regression model, this study analyzes data from 30 countries in the Asia-Pacific region over the 2008–2022 period. Based on secondary data sourced from the World Bank, the estimation results clearly demonstrate that population aging is detrimental to a country's economic growth, whereas public health expenditure yields a significant positive impact on economic growth in the Asia-Pacific region. This research is expected to serve as a reference for policymakers in designing strategies to enhance national resilience in facing demographic structural changes.